The Influence of Profitability, Executive Character, and Company Size on Tax Avoidance - Sugiharto Sugiharto; Carlos Afonso Baretto; Aditya Ramadhani Kurniawan (AKRUAL: JURNAL AKUNTANSI, 2025)
Research Background: A Limited Liability Company (PT) that has deposited or traded at least 40% of its shares on the IDX from the total shares it owns and has fulfilled certain requirements is an example of a domestic corporate taxpayer. Companies, especially Limited Liability Companies that have entered the capital market or the Indonesian Stock Exchange, have become taxpayers and are required to pay, withhold and collect tax.Introduction/ Main Objectives: This study aims to analyze the effect of profitability, executive character and company size on tax avoidance with leverage as an intervening variable. Methods: The population of this study consisted of 220 zompanies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024, with sample of 61 companies selected through a purposive sampling method. The data used are secondary data that are quantitative in nature. The analysis method used is path analysis to identify direct and indirect effect using SPSS 22 Software. Results: The data was proceed using path analysis and the results showed that profitability, executive character and company size did not affect the company’s tax avoidance with leverage as and intervening variable.